Registration of RMBUP‐C4, a Random‐Mated Population with Gossypium barbadense L. Alleles Introgressed into Upland Cotton Germplasm. Issue 2 (15th February 2013) - Jenkins, J. N.; McCarty, J. C.; Gutiérrez, O. A.; Hayes, R. W.; Jones, D. C.
Abstract : RMBUP‐C4 (random‐mated barbadense Upland population cycle 4) (Reg. No. GP‐961, PI 665950) is a unique random‐mated germplasm population of Upland cotton ( Gossypium hirsutum L.) with introgression of G. barbadense L. alleles. This population involved five cycles of random mating beginning with 53 top‐crossed F1 lines. The germplasm was developed through cooperative research by the USDA‐ARS, the Mississippi Agricultural and Forestry Experiment Station, and Cotton Incorporated. The cultivars 'Sure‐Grow 747' (PVP 9800118), 'PSC 355', and 'FM 966' (PVP 200100209) were each crossed with 18 lines with chromosome substitution from G. barabadense (CS‐B); however, the seed of PSC 355 × CS‐B22sh was lost, resulting in 53 topcross populations. The bulked‐pollen method of pollination was used in the development, and there were five cycles of random mating with the intercrossing of F1 lines considered as cycle zero. After each cycle of random mating, F1 lines were combined on the basis of the original CS‐B parents, thus producing 18 individual populations. These were planted as 18 individual populations and randomly mated among populations each additional cycle. Because the CS‐B lines were each euploid chromosome substitution lines with entire chromosomes or arms from G. barbadense substituted into Upland, we should have achieved considerable introgression of alleles from G. barbadense into this randomly mated population. This population should be of value to cotton breeders and geneticists across the U.S. Cotton Belt as a unique population with G. barbadense introgression.